Mengoptimalkan pengetahuan tim pemberdayaan kesejahteraan keluarga (PKK) dalam produksi kue tradisional di era modern: studi kasus di Malang - Gumoyo Mumpuni Ningsih; Harun Rasyid (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2024)
The traditional cake business is very promising. Processing raw materials into semi-finished or partially finished goods produces products with high market value. Therefore, this study presents the results of counseling aimed at improving the knowledge of PKK mothers regarding traditional cake production. The purpose of this research is to optimalize the knowledge of mothers about the making of traditional cakes, production management, financial management, and marketing management. The research used descriptive qualitative analyses approach which was conducted in PKK RT 03/RW 02, Tlogo Mas Village, Lowok Waru Subdistrict, Malang City. The study lasted for 8 months. The population in this study was PKK mothers from RT 03/RW 02 in Tlogo Mas Village, Malang. Sampling was done through census (total sampling) with a sample size of 36 people. The data source used was primary data, namely the results of counseling and interviews with PKK mothers. The research results show that PKK mothers have good knowledge in the production of traditional cakes and are interested in running the business after receiving counseling. They have started implementing marketing management by organizing cake production according to market demand and learning to manage finances by recording production costs. However, there are still shortcomings in calculating labor and transportation costs. Nevertheless, these steps contribute positively to increasing family income and business development in the future.